MICROSTRUCTURAL EVOLUTION AND MECHANICAL PERFORMANCE OF SMAW DISSIMILAR WELDS BETWEEN ASTM A36 AND AISI 316 WITH E316-16 ELECTRODE AT DIFFERENT WELDING CURRENTS - Nurhabibah Paramitha Eka Utami; Hendri Chandra; Diah Kusuma Pratiwi; Ellyanie Ellyanie; Astuti Astuti; Wisnu Hafiz Prastyanto; Muhammad Ihsan Riady; Dyos Santoso; M. A. Ade Saputra (Indonesian Journal of Engineering and Science, 2025)
This study investigates the effect of welding current on the microstructural evolution and mechanical performance of Shielded Metal Arc Welded (SMAW) dissimilar lap joints between ASTM A36 carbon steel and AISI 316 stainless steel using an E316-16 electrode. Welding was performed at three different currents, namely 60 A, 70 A, and 80 A, to evaluate their influence on microstructure, hardness distribution, and impact toughness. Microstructural characterization was conducted using optical microscopy to examine phase formation and grain morphology in the weld metal and heat-affected zone (HAZ). Mechanical properties were evaluated through Vickers hardness testing and Charpy impact testing. The results show that increasing welding current leads to higher heat input, promoting the formation of finer pearlite and acicular ferrite in the weld metal, along with an expansion of the HAZ. These microstructural changes resulted in increased hardness, with the highest average hardness value of 343.32 HV observed in the weld metal at 80 A. Impact test results indicated that higher welding currents enhanced impact toughness due to the interlocking morphology of acicular ferrite, which effectively retards crack propagation. However, localized grain coarsening was observed near the fusion boundary, particularly within the HAZ. Overall, a welding current of 80 A provided the most favorable combination of hardness and impact toughness, indicating its suitability for optimizing the mechanical performance of SMAW dissimilar welded joints between ASTM A36 and AISI 316.